Quantifying Impact of HIV Receptor Surface Density Reveals Differences in Fusion Dynamics of HIV Strains - Anthony Gerg; Hana M. Dobrovolny (Viruses)
Human Immunodeficiency Virus (HIV) Type-1 has been studied heavily for decades, yet one area that is still poorly understood is the virus’ ability to cause cell–cell fusion. In HIV, the fusion process is mediated by viral surface glycoproteins that bind to CD4 cell receptors. This virus-mediated cell fusion creates multi-nucleated cells called syncytia that can affect infection dynamics. Syncytia formation is often studied using a cell–cell fusion assay, in which donor cells expressing the viral surface protein fuse with acceptor cells expressing the cell receptor. A mathematical model capable of reproducing the dynamics of the cell–cell fusion assay was recently developed and can be used to quantify changes in syncytia formation. In this study, we use this mathematical model to quantify the changes in syncytia formation in HIV as the surface density of the glycoproteins is varied. We find that we need to modify the model to explicitly include a density-dependent syncytia formation rate that allows us to capture the dynamics of the cell–cell fusion assay as the density of the glycoproteins changes. With this modification, we find that cell–cell fusion of the HXB2 strain, which uses the CXCR4 coreceptor, shows a threshold-like behavior, while cell–cell fusion of the Sf162 strain, which uses the CCR5 co-receptor, shows a more gradual change as surface density decreases.